1976
DOI: 10.1021/bi00668a009
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the carbohydrate units of immunoglobulins. 1. Purification and properties of galactosyltransferases from swine mesentary lymph nodes

Abstract: Galactosyltransferase (UDPgalactose:glycoprotein galactosyltransferase EC 2.4.1.22) was isolated from swine mesentary lymhromatography on Sepharose 4B colums containing covalently bound p-aminophenyl-beta-D-N-acetylglucosamine. The homogenous enzyme showed a single band on disc gel electrophoresis and had a specific activity of 35 nmol min-1 (mg of protein)-1 at 37 degrees C. A molecular weight of 57 000 was obtained by exclusion chromatography, sucrose density centrifugation, and sodium dodecyl sulfate-gel el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…It was further assumed that the volume of each Golgi compartment (V) was equal to 10 -13 ml, as estimated using electron microscopy of Golgi cisternae [33]. In the cases that multiple glycan reactants are substrates for the same enzyme, the values were assumed to be equal for each glycan (Table 2) [16], [21], [23], [25]-[27], [29], [34]-[36].…”
Section: Methodsmentioning
confidence: 99%
“…It was further assumed that the volume of each Golgi compartment (V) was equal to 10 -13 ml, as estimated using electron microscopy of Golgi cisternae [33]. In the cases that multiple glycan reactants are substrates for the same enzyme, the values were assumed to be equal for each glycan (Table 2) [16], [21], [23], [25]-[27], [29], [34]-[36].…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that the lactose synthetase and other p1-4GalTs are activated by Mn2+, which is involved in maintaining the structural integrity of the enzyme, and the optimal Mn2+ concentrations of these enzymes were in the range of 10-15 mM [2][3][4][5][6][7][8][9][10][11]241. The pCMGTl-directed P1-4GalT in COS-1 cells was also activated by Mn2' and its optimal Mn2+ concentration was about 10 mM.…”
Section: Activation Q F U Fli-4gnlt H-v Mn2' Ionmentioning
confidence: 99%
“…TaMe 1. Degradation rates (t 89 of brush border (BBM) and basolateral membrane (BLM) phospholipids determined using 2-3H acetate and uniformly labeled 3H-glycerota carried out using standard kinetic assays as previously reported from our laboratory [16,17] and galactosyltransferase was assayed according to the method of Rad et al [19]. Lipids from approximately 1 mg of membrane protein were extracted in 6 ml of chloroform/methanol (1 : 2 vol/vol) isolated and quantitated as we have previously described [16,17].…”
Section: Preparation and Characterization Of Membranesmentioning
confidence: 99%